Item analysis of objective structured clinical examination (OSCE) assessment rubrics for undergraduate pharmacy students - Mohamed Nazar, Nor Ilyani; Zin, Che Suraya; Ab Rahman, Norny Syafinaz (Wolters Kluwer - Medknow, 2020)
Introduction: Objective Structured Clinical Examination (OSCE) is one of the assessments that objectively evaluate the students’ competency in handling the specific hands-on clinical tasks. The rubrics of the assessment is very critical to be evaluated ensuring its validity. Objectives: This study aimed to evaluate the usefulness of the item analysis method in objectively analyse the validity of the assessment rubrics developed for OSCE in the field of pharmacy. Materials and Methods: Fifty-four (54) students participated in the OSCE and were divided into three groups of the concurrent session with four active stations and two preparatory stations. The examiners were well-trained on the assessment rubrics before the examination for standardization. The questions and assessment rubrics were developed and vetted earlier in a group of vetting committee who were expert in the field of pharmacy practice and languages. There were four (4) tasks in the active stations namely; i) Insulin device counselling, ii) Extemporaneous preparation of spironolactone syrup, iii) Unit of dose supply and iv) Psychotropic drugs recording and supply. Results: Majority of the items in the rubrics showed acceptable levels of discrimination (>0.3) and difficulty index (0.25–0.85) except for a few items that need to be reviewed and improvised literally or constructively. Conclusion: Item analysis method is useful in analysing the validity of the assessment rubrics developed for OSCE in pharmacy field.